Prevalence of Genotypes That Determine Resistance of Staphylococci to Macrolides and Lincosamides in Serbia - Mišić, Milena; Čukić, Jelena; Vidanović, Dejan; Šekler, Milanko; Matić, Sanja; Vukašinović, Mihailo; Baskić, Dejan (Frontiers in Public Health, 2017)
Macrolides, lincosamides, and streptogramins (MLS) resistance genes are responsible for resistance to these antibiotics in Staphylococcus infections. The purpose of the study was to analyze the distribution of the MLS resistance genes in community- and hospital-acquired Staphylococcus isolates. The MLS resistance phenotypes [constitutive resistance to macrolide–lincosamide–streptogramin B (cMLSb), inducible resistance to macrolide–lincosamide–streptogramin B (iMLSb), resistance to macrolide/macrolide–streptogramin B (M/MSb), and resistance to lincosamide–streptogramin A/streptogramin B (LSa/b)] were determined by double-disc diffusion method. The presence of the MLS resistance genes (ermA, ermB, ermC, msrA/B, lnuA, lnuB, and lsaA) were determined by end-point polymerase chain reaction in 179 isolates of staphylococci collected during 1-year period at the Center for Microbiology of Public Health Institute in Vranje. The most frequent MLS phenotype among staphylococcal isolates, both community-acquired and hospital-acquired, was iMLSb (33.4%). The second most frequent was M/MSb (17.6%) with statistically significantly higher number of hospital-acquired staphylococcal isolates (p < 0.05). MLS resistance was mostly determined by the presence of msrA/B (35.0%) and ermC (20.8%) genes. Examined phenotypes were mostly determined by the presence of one gene, especially by msrA/B (26.3%) and ermC (14.5%), but 15.6% was determined by a combination of two or more genes. M/MSb phenotype was the most frequently encoded by msrA/B (95.6%) gene, LSa/b phenotype by lnuA (56.3%) gene, and iMLSb phenotype by ermC (29.4%) and ermA (25.5%) genes. Although cMLSb phenotype was mostly determined by the presence of ermC (28.9%), combinations of two or more genes have been present too. This pattern was particularly recorded in methicillin-resistant Staphylococcus aureus (MRSA) (58.3%) and methicillin-resistant coagulase-negative staphylococci (MRCNS) (90.9%) isolates with cMLSB phenotype. The msrA/B gene and M/MSb phenotype were statistically significantly higher in hospital-acquired than community-acquired staphylococci strains (p < 0.05). There are no statistically significant differences between staphylococci harboring the rest of MLS resistance genes acquired in community and hospital settings (p > 0.05). The prevalence of iMLSb phenotypes may change over time, so it is necessary to perform periodic survey of MLS resistance phenotypes, particularly where the D-test is not performed routinely.